Mapping a geothermal anomaly using apatite (U‐Th)/He thermochronology in the Têt fault damage zone, eastern Pyrenees, France. (14th October 2019) - Milesi, Gaétan; Soliva, Roger; Monié, Patrick; Münch, Philippe; Bellanger, Mathieu; Bruguier, Olivier; Bonno, Michael; Taillefer, Audrey; Mayolle, Sylvain
Abstract: (U‐Th)/He ages on apatite obtained in the vicinity of the Têt fault hydrothermal system show a large variability. In the inner damage zone adjacent to the fault core, where fluid flows are concentrated, AHe ages display a large scatter (3–41 Ma) and apatite ageing. Samples from the outer damage zone show young ages with less dispersion (0.9–21.1 Ma) and apatite rejuvenation. Outside the damage zone, ages are consistent with the regional exhumation history between 20 and 12 Ma. The important age dispersion found in the damage zone is interpreted as the result of 4 He mobility during fluid infiltration. Our results show that thermochronological data close to a fault should be interpreted with caution, but may offer a new tool for geothermal exploration.